Sex‐specific aging in animals: Perspective and future directions. Issue 2 (23rd January 2022) - Bronikowski, Anne M.; Meisel, Richard P.; Biga, Peggy R.; Walters, James R.; Mank, Judith E.; Larschan, Erica; Wilkinson, Gerald S.; Valenzuela, Nicole; Conard, Ashley Mae; de Magalhães, João Pedro; Duan, Jingyue (Ellie); Elias, Amy E.; et al.
Abstract: Sex differences in aging occur in many animal species, and they include sex differences in lifespan, in the onset and progression of age‐associated decline, and in physiological and molecular markers of aging. Sex differences in aging vary greatly across the animal kingdom. For example, there are species with longer‐lived females, species where males live longer, and species lacking sex differences in lifespan. The underlying causes of sex differences in aging remain mostly unknown. Currently, we do not understand the molecular drivers of sex differences in aging, or whether they are related to the accepted hallmarks or pillars of aging or linked to other well‐characterized processes. In particular, understanding the role of sex‐determination mechanisms and sex differences in aging is relatively understudied. Here, we take a comparative, interdisciplinary approach to explore various hypotheses about how sex differences in aging arise. We discuss genomic, morphological, and environmental differences between the sexes and how these relate to sex differences in aging. Finally, we present some suggestions for future research in this area and provide recommendations for promising experimental designs. Abstract : Sex difference in aging occurs across the animal kingdom, but there is considerable variation and they are not universal. The processes leading to sex‐specific aging are poorly understood and might originate in sex‐specific genome architecture, organismal biology, or environmental interactions. Here, we take a comparative approach to review the various hypotheses and suggest promising areas of research for further study.